Pengaruh Citra Destinasi dan Negative Electronic Word of Mouth (Negative E-WOM) terhadap Niat Berkunjung Kembali ke Pantai Kuta, Kecamatan Kuta, Bali - Triana Putra, I Nyoman; Darsana, I Made; Made Sabda Nirmala, Bagus (Penerbit Lafadz Jaya, 2026)
This study aims to examine the influence of destination image and negative electronic word of mouth (negative e-WOM) on tourists’ revisit intention to Kuta Beach, Bali. A quantitative approach with explanatory research design was employed. Data were collected through questionnaires from 100 respondents who had visited Kuta Beach and actively used social media, selecting using purposive sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that destination image has a positive and significant effect on revisit intention, whereas negative e-WOM has a negative but insignificant effect. The model demonstrates moderate explanatory power (R² = 0.513), no multicollinearity issues (VIF < 5), and good predictive relevance (Q² > 0). These findings indicate that destination image is the primary determinant of tourist loyalty, while the influence of negative e-WOM tends to be contextual and indirect. Practically, this study highlights the importance of improving tourism experience quality, particularly in terms of cleanliness, infrastructure, and comfort, in order to strengthen destination image and enhance tourists’ revisit intention.